Pengaruh Diversifikasi Pendapatan, Modal Intelektual, Dan Pengungkapan Manajemen Risiko Terhadap Nilai Perusahaan: Studi Empiris pada Bank Umum Konvensional yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2020 - Pertiwi, Siska Puspa; Suhartini, Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Company value describes the quality of a company. There are several factors that affect company value, including, the recent trend of diversification strategy, business risk, and how the company’s resource is well managed. This study aims to investigates the impact of income diversification, intellectual capital and enterprise risk management on company value. Based on purposive sampling criteria obtained 25 observations of conventional banking listed on Indonesia Stock Exchange during 2015-2020. Data analysis technique used in this study is Partial Least Square (PLS) software SmartPLS (3.2.9). Findings showed that there is no significant impact of income diversification on company value. Meanwhile, intellectual capital has significant positive impact on company value, and enterprise risk management has significant negative impact on company value. The result of this study can be used as further study to determine the amount of company value influenced by income diversification, intellectual capital, and risk management so that it provides a competitive strategy. It is important for the company to maintain their resources management as it had been created value in the company. In addition, it is recommended for management to take more concern how the company mitigates the risks so that it provides a positive signal for investors.